Left atrial shape predicts recurrence after atrial fibrillation catheter ablation. (19th June 2018) - Bieging, Erik T.; Morris, Alan; Wilson, Brent D.; McGann, Christopher J.; Marrouche, Nassir F.; Cates, Joshua
Abstract: Introduction: Multiple markers left atrium (LA) remodeling, including LA shape, correlate with outcomes in atrial fibrillation (AF). Catheter ablation is an important treatment of AF, but better tools are needed to determine which patients will benefit. In this study, we use particle‐based modeling to quantitatively assess LA shape, and determine to what degree it predicts AF recurrence after catheter ablation. Methods and results: There were 254 patients enrolled in the DECAAF study who underwent cardiac magnetic resonance imaging of the LA prior to AF ablation and were followed for recurrence for up to 475 days. We performed particle‐based shape modeling on each patient's LA shape. We selected shape parameters using the LASSO method and factor analysis, and then added them to a Cox regression model, which included multiple clinical parameters and LA fibrosis. We computed Harrell's C‐statistic with and without shape in the model. We used the model to stratify patients into recurrence risk classes by both shape and shape and fibrosis combined. Three shape parameters were selected for inclusion. The C‐statistic increased from 0.68 to 0.72 when shape was added to the model (P < 0.05). Visualized shapes showed that a more round LA shape with a shorter, more laterally rotated appendage was predictive of recurrence. Conclusion: LA shape is an independent predictor of recurrence after AF ablation. When combined with LA fibrosis, shape analysis using PBM may improve patient selection for ablation.